Effect of herbal feed supplements on milk yield and composition in crossbred cows in Tripura - DAS, TAPAN KUMAR; DEBNATH, BIKAS CHANDRA; SARKAR, BIJOY KUMAR; DE, ANKAN; MAINI, SHIVI (The Indian Journal of Animal Sciences, 2017)
The study was conducted to evaluate the effect of feeding 5 herbal preparations on the milk yield and composition of crossbred cows. Thirty five lactating cows in their first-third lactation were taken for the experiment. The cows were divided into 7 groups with 5 cows in each group on the basis of average milk yield (8.70±0.08 kg/d). The experiment was conducted for 90 days, partitioned into pre-treatment period (15 days), treatment period (60 days) and post treatment observation period (15 days). The cows in group C0 were not given any supplement and acted as control. In addition to normal routine feeds and fodders, cows in groups T1 and T2 were given either Restobal @ 50ml twice daily for 5 days/month or Ruchamax @ 15 g/ day for 8 days/month, respectively for 60 days treatment period. The cows in groups T3, T4 and T6 were given either Payaboon @ 500 g/ton, Payaboon @ 1 kg/ton, Optrium @ 500 g/ton/ day, respectively for 60 days treatment period. In group T5, cows were given Payapro @ 4 bolus/day for 15 consecutive days commencing after 15 days pre-treatment period. T5 group showed comparatively higher total milk yield than the control and other groups. Average milk yield (kg/d) during the supplementation period was slightly higher in T5 followed by T2 and T6. T5 group showed lowest trend of reduction in milk yield during treatment period. Average milk yield (kg/d) during post supplementation period was also higher in T5. Milk protein and fat (%) were higher in T1 and T3 than the control and other treatment groups. Total solid and SNF (%) showed higher trend in T1. At 15 day of supplementation, milk yield increased in all the treatment groups compared to control (8.38) and it was highest in T5 (9.69). The milk yield decreased gradually thereafter but the rate of reduction was comparatively lower in T24, T5 and T6 than the control. Milk constituents showed significant variations among different weeks in different groups. Hence it can be concluded that herbal preparations can increase the productivity in lactating dairy cows with no deleterious effect on general health.